A secure key distribution protocol based on hash functions and a quantum-authenticated channel using 6DP (KDP-6DP) - Al-Khateeb, Khalid A. Saeed; Abdul Majeed, Mohammed Munther; Ridza, Mohamed; Saeb, Magdy M. (2010)
Security is the most tedious problem in highly sensitive communications. Quantum security is the key issue in solving the problem. A key distribution protocol based on the use of hash functions is proposed. The essential part of the protocol depends on sending a string of random characters from sender to receiver. Then, a selected hash or a cascade of two hash functions and a long-term shared secret are used to construct the key. Consequently, the session key is generated on-site by independently applying a hash function on the random string at the sender and receiver sides. This protocol requires a reliable method of authentication. Therefore, it is further proposed to use an out-of-band authentication methodology based on the deterministic six-state quantum authentication protocol that is referred to as 6DP.